2019
DOI: 10.3389/fnmol.2019.00031
|View full text |Cite
|
Sign up to set email alerts
|

Co-administration of Anti microRNA-124 and -137 Oligonucleotides Prevents Hippocampal Neural Stem Cell Loss Upon Non-convulsive Seizures

Abstract: Convulsive seizures promote adult hippocampal neurogenesis (AHN) through a transient activation of neural stem/progenitor cells (NSPCs) in the subgranular zone (SGZ) of the dentate gyrus (DG). However, in a significant population of epilepsy patients, non-convulsive seizures (ncSZ) are observed. The response of NSPCs to non-convulsive seizure induction has not been characterized before. We here studied first the short-term effects of controlled seizure induction on NSPCs fate and identity. We induced seizures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 61 publications
0
19
1
Order By: Relevance
“…Images were obtained using the microscope Nikon Eclipse at 20x or 40x magnification and quantification was performed using a Cell-counter plugin in Fiji. DAB staining was performed as previously reported (Bielefeld et al, 2019). Briefly, sections were incubated with peroxidase block (Vectashield), permeabilized with 0.3% PBS-Triton X (PBS-T) and 0.1% PBS-T.…”
Section: Immunostaining Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Images were obtained using the microscope Nikon Eclipse at 20x or 40x magnification and quantification was performed using a Cell-counter plugin in Fiji. DAB staining was performed as previously reported (Bielefeld et al, 2019). Briefly, sections were incubated with peroxidase block (Vectashield), permeabilized with 0.3% PBS-Triton X (PBS-T) and 0.1% PBS-T.…”
Section: Immunostaining Analysismentioning
confidence: 99%
“…Kainic Acid to elicit tonic, non-convulsive epileptic seizures, was administered as described before (Bielefeld et al, 2019). Briefly, 50nL of 2.22mM Kainic Acid dissolved in PBS (pH 7.4) was injected bilaterally into the hippocampus at the following coordinates (AP -2.0, ML +/-1.5, DV -2.0 mm) (between 9AM and 1PM).…”
Section: Kainic Acid Administration Single Cell Suspension and Enrichment Of Anpcs By Facsmentioning
confidence: 99%
“…Brief (3-7 sec) abnormalities were reported by others where they could be as frequent as 100 per hr (Kim et al, 2018; Sandau et al, 2019; Lai et al, 2020). Sometimes the EEG examples that were published suggested trains of spikes or epileptiform activity occurred in the wks after IHKA, but seizures were either rare, not shown, or the evidence that they occurred was not strong (e.g., Kiasalari et al, 2016; Zhu et al, 2016; Runtz et al, 2018; Bielefeld et al, 2019; Li et al, 2020). One study that described methods for IHKA in mice concluded that IHKA did not lead to epilepsy (Bielefeld et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Key signaling pathways acting as regulators of NSC quiescence include, among others, Notch (Ehm et al, 2010 ; Imayoshi et al, 2010 ; Lugert et al, 2010 ), ephrins in endothelial cells (Ottone et al, 2014 ), cadherins in ependymal cells (Porlan et al, 2014 ), BMP, WNT (Li and Clevers, 2010 ; Mira et al, 2010 ), GABAergic (Song et al, 2012 ; Giachino et al, 2014 ), and glutamatergic signaling (Lugert et al, 2010 ; Sierra et al, 2015 ; Bielefeld et al, 2019 ). For an extensive overview of all signaling pathways and proteins involved in maintaining aNSC quiescence, we refer to an excellent recent review (Urbán et al, 2019 ).…”
Section: Micrornasmentioning
confidence: 99%